O treino cognitivo no transtorno do espectro autista - Teodoro, Priscilla Custódia da Silva (2023)
Objective: to carry out two systematic reviews of publications from the last 20 years regarding the efficiency of cognitive training of children and adolescents with autism spectrum disorder in aspects of working memory and attention processes. Method: The review followed the guidelines of the PRISMA model. The VHL, Embase, PsycInfo, PubMed and Web of Science databases were used for the first article under the descriptors autism spectrum disorders or autism or asperger syndrome and cognitive training, and for the second, the platforms PubMed, PsycInfo, BVS and Embase, with the descriptors: autism or autism spectrum disorders and cognitive training. Results: In the first study, 4.172 articles were located, of which 4.165 were excluded in the selection process, and seven were considered eligible to compose the sample. In the second article, 4.034 articles were located, of which 4.024 were excluded and 10 were selected for the sample. Contradictory results were observed in both bibliographic surveys, with results strengthened by greater observance. The tested cognitive training is potentially useful for improving working memory and attentional processes, leading to better functioning of behavioral, social and academic aspects. Conclusion: In view of the results found, it was observed the importance that cognitive training has on the working memory and the attention processes of children and adolescents with ASD, as well as the potential that an intervention can generate to control the symptomatology of the disorder and improving the quality of life of this population.